Peningkatan Caring Islami Pada Perawat - Yousriatin, Fajar; Kirana, Wahyu; Anggreini, Yunita Dwi; Juliana, Diena; Safitri, Dewin; Afrianti, Femi Yuli (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Nurses are the largest human resource in health services in hospitals, where nurses work 24 hours a day in rotation and continuously to provide comprehensive and professional nursing care and are ready to help patients at any time. In an effort to improve the quality of health services, nurses are required to provide the best service in the form of caring behavior or caring attitude towards others. Caring behavior given by nurses to clients can increase patient satisfaction, especially by incorporating Islamic values where Islamic values are rahmatan lil alamin or compassion for all beings regardless of race, ethnicity, nation, language and religion. RSU Yarsi Pontianak is an Islamic-based hospital in providing nursing care. In accordance with the hospital's vision "to become a hospital based on Islam with high-quality and international standard health services", Yarsi General Hospital prioritizes services that have Islamic values, especially in providing nursing care. The purpose of this community service is to increase nurses' knowledge of the application of Islamic caring at YARSI Pontianak General Hospital (RSU). Community service activities are carried out through several stages, namely the preparation, implementation and evaluation stages. The results of the initial measurement of nurses' knowledge about Islamic caring found that most nurses had sufficient knowledge, namely 55%. Whereas after being given training on Islamic caring, most of the nurses had good knowledge, namely 80%. Training is an effective and efficient activity to increase nurses' knowledge about Islamic caring. Based on the results of community service, there was an increase in nurses' knowledge after being given Islamic caring training.